Thyme (Thymus vulgaris) as a Natural Feed Additive in Poultry Nutrition: Enhancing Performance, Health, and Carcass Traits - Abd El-Aziz, A.; Buonaiuto, G.; Yıldırım, A.; El-Sabrout, K. (Tropical Animal Science Journal, 2026)
The worldwide demand for poultry products is on the rise, thus emphasizing the necessity of natural additives in feed that boost productivity but do not compromise animals’ health and food safety. Thyme (Thymus vulgaris) is a medicinal and culinary herb that has attracted attention as a phytogenic feed additive because of its bioactive compounds such as thymol and carvacrol. This review aims to summarize the impact of thyme supplementation in poultry, namely in broilers, layers, and quail, through leaves, powders, essential oils, and aqueous extracts. Thyme has been shown to improve growth performance, feed efficiency, and carcass traits at inclusion rates of 0.5%-2% for powders and 0.5%-1% for essential oils. Thyme supplementation influences reproductive performance, egg quality, and semen parameters; moreover, it also works as an immune modulator by increasing IgG, IgM, interferon-gamma, and interleukin-10. Antioxidant defense is strengthened through enhanced activities of glutathione, superoxide dismutase, and glutathione S-transferase, along with reduced levels of malondialdehyde. Additionally, thyme showed favorable effects on serum lipid profile and gut health by stimulating protective species of Lactobacillus and suppressing pathogens (such as Escherichia coli). Mechanistic data suggest regulation of inflammatory cytokines and intestinal barrier genes. Thyme is a promising candidate for replacing antibiotics as growth promoters in tropical poultry systems, at levels of 0.5%-2% thyme powder and 100-200 mg/kg essential oil. To fully realize the potential of thyme as a sustainable alternative to antibiotics in poultry production, future studies should explore optimal dosing, mechanistic studies of the target site of action, stress mitigation capacity, long-term production impacts, and economic viability.